Flooded River - Unknown:::Creator::::::::::::
Number 3 of 10 Steinbeck locations: A flooded river near some concrete pilings. Others in this series are numbers 0-064, 0-809, 0-811, 0-812, 0-813, 0-814, 0-815, 0-816, 0-817.